2012
DOI: 10.5296/ijld.v2i3.1756
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Job Satisfaction and HR Practices, an Empirical Research of Different Sectors of University Teachers in Pakistan

Abstract: A number of researchers focus on the issue of HR practices and their impact on performance of employees particularly on developed countries. Few researches are there for the implication of these practices in developing countries. The current research focus on relationship between job satisfaction of university employees and focus HR practices which are compensation, promotion, empowerment and performance evaluation practice. It also focus on demographic attributes impact on job satisfaction and HR practices. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
0
8
1
Order By: Relevance
“…For example, the higher the level of job satisfaction, the more workers are likely to have a positive attitude toward their job (Wang & Feng, 2003), and the more they can commit to the organization (Brown & Peterson, 1993). The interrelation between job satisfaction and different managerial practices in the public sector has been discussed at length (Khan, Ghauri, & Akram, 2012;Sokoya, 2000). In order to increase satisfaction of public employees, many public sector organizations have emphasized the development of motivational strategies to enhance employees' satisfaction for performance efficiency as well.…”
Section: Importance Of Job Satisfactionmentioning
confidence: 99%
“…For example, the higher the level of job satisfaction, the more workers are likely to have a positive attitude toward their job (Wang & Feng, 2003), and the more they can commit to the organization (Brown & Peterson, 1993). The interrelation between job satisfaction and different managerial practices in the public sector has been discussed at length (Khan, Ghauri, & Akram, 2012;Sokoya, 2000). In order to increase satisfaction of public employees, many public sector organizations have emphasized the development of motivational strategies to enhance employees' satisfaction for performance efficiency as well.…”
Section: Importance Of Job Satisfactionmentioning
confidence: 99%
“…ISSN: 2012-7227 Various research findings help to prove some of the relationship and association of HRM functions with job satisfaction. Relationship or association of compensation of workers with their job satisfaction was one finding of the study and Rasouli et al (2013), Ting (1997), Absar et al (2010), Hock (2011), Jeet and Sayeeduzzafar (2014), Droussiotis and Austin (2007), Tasema and Soeters (2006), Delaney and Huselid (1996), Syed and Yah (2012), Masoodul et al (2013), Oyeniyi et al (2014) Sarker (2014, Khan et al (2012), Ray and Ray (2011) and Niazi (2014) stressed that there is a relationship or association of compensation with job satisfaction. Another finding of the study is that there is a positive and strong relationship and association of HRM practices on job satisfaction and this finding is confirmed by Jeet and Sayeeduzzafar (2014), Bradley, Petrescu and Simmons (2004), Delaney and Huselid (1996), Oyeniyi et al (2014), Sarker (2014), Garcia (2005), Absar et al (2010), Rasouli et al (2013), Majumder (2012, Ray andRay (2011), Niazi (2014) and Ijiqu (2015).…”
Section: Discussion and Recommendationmentioning
confidence: 82%
“…However, when considering the extrinsic job satisfaction, it has a positive and strong correlation with HRM practices and positive and moderate association with HRM practices. As Khan et al (2012), Wright et al in 2003(cited by Omar et al 2013), Spector in 1997(cited in Omar et al 2013), Huselid in 1995 (cited by Omar et al 2013) and Petrescu and Simmons (2008) pointed out there is a positive and strong correlation between HRM practices with job satisfaction. ISSN: 2012-7227 Various research findings help to prove some of the relationship and association of HRM functions with job satisfaction.…”
Section: Discussion and Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…Work load was the most strongly associated with job satisfaction followed by the perception about colleagues, status of job, management support, and remuneration and development. Khan et al (2012) found that male faculty members of the university are more satisfied than the female faculty member. HRM practices that are offered by the universities do not satisfy male and female equally.…”
Section: Review Of Literaturementioning
confidence: 99%